Developing a Motivation Scale for Engineering Studies in a Francophone Context - Chédru, Marie (Mesure et évaluation en éducation, 2019)
Based on self-determination theory, this research presents the development of a scale to assess motivation for engineering studies in a Francophone context. Three phases of data collection were conducted (N = 462, 545 and 864) for a total of 1871 engineering students (59.2% female). Results from both exploratory and confirmatory factor analyses support a seven-factor structure for the scale: 1) intrinsic motivation, extrinsic motivations characterised by 2) identified regulation – altruism, 3) introjected regulation – ego, 4) introjected regulation – conscience, 5) external regulation – security, 6) external regulation – social prestige and, finally, 7) amotivation. The dimensions of altruism and security are specific to engineering studies. The scale meets generally accepted criteria for reliability and verifies different types of validity evidence.